The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0165025419876360
|View full text |Cite
|
Sign up to set email alerts
|

Examining the measure of student engagement in the classroom using the bifactor model: Increased validity when predicting misconduct at school

Abstract: Few studies have used exploratory factor analysis (EFA) and exploratory bifactor factor analysis (EBFA) to define a baseline factor structure model checking the construct-relevant psychometric multidimensionality of student engagement. This study was conducted on a sample of 3,374 students in France, Wallonia-Brussels Federation, and Luxembourg by using EFA and EBFA, and by comparing four confirmatory factor models of student engagement in the classroom. Results indicated the relevance of a bifactor model to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Wang et al (2016), for example, found that student engagement in maths and science could be best represented by a bi‐factor model with a general student engagement factor and specific factors of behavioural, cognitive, emotional and social engagement. Similar findings were also reported by Stefansson et al (2016) and Dierendonck et al (2020) who converged on a bi‐factor model of student engagement at the school and classroom levels respectively, with a general engagement factor and three specific components of behavioural, cognitive and affective engagement. However, these studies were conducted in school contexts with face‐to‐face learning modes and did not account for the concern about the conceptual ambiguity among student engagement components to which the next discussion turns.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Wang et al (2016), for example, found that student engagement in maths and science could be best represented by a bi‐factor model with a general student engagement factor and specific factors of behavioural, cognitive, emotional and social engagement. Similar findings were also reported by Stefansson et al (2016) and Dierendonck et al (2020) who converged on a bi‐factor model of student engagement at the school and classroom levels respectively, with a general engagement factor and three specific components of behavioural, cognitive and affective engagement. However, these studies were conducted in school contexts with face‐to‐face learning modes and did not account for the concern about the conceptual ambiguity among student engagement components to which the next discussion turns.…”
Section: Literature Reviewsupporting
confidence: 88%
“…The multidimensional framework applied in this study affords researchers and practitioners alike an easy‐to‐administer and validated measure to move beyond solely focusing on students' behavioral engagement in afterschool spaces. It is important to note that students' experiences of engagement are best understood in a bifactor model, which resembles prior work around engagement in formal school settings (Bae et al, 2020; Dierendonck et al, 2020; M. T. Wang, Fredricks, et al, 2019), and in mathematics and science contexts more specifically (Bae & DeBusk‐Lane, 2019; Wang et al, 2016). Further, in alignment with Dierendonck and colleagues' (2020) interpretation of classroom engagement, our results highlight how student engagement in afterschool spaces includes a unidimensional construct that also consists of small specific latent dimensions (i.e., cognitive engagement) that need to be identified to achieve a well fitting model solution (see Brown, 2015, p. 301).…”
Section: Discussionmentioning
confidence: 84%
“…It is important to note that students' experiences of engagement are best understood in a bifactor model, which resembles prior work around engagement in formal school settings (Bae et al, 2020; Dierendonck et al, 2020; M. T. Wang, Fredricks, et al, 2019), and in mathematics and science contexts more specifically (Bae & DeBusk‐Lane, 2019; Wang et al, 2016). Further, in alignment with Dierendonck and colleagues' (2020) interpretation of classroom engagement, our results highlight how student engagement in afterschool spaces includes a unidimensional construct that also consists of small specific latent dimensions (i.e., cognitive engagement) that need to be identified to achieve a well fitting model solution (see Brown, 2015, p. 301). This similarity in the modeling of engagement suggests that the structure of adolescent engagement experiences in afterschool spaces parallel those in more formal educational settings, a helpful understanding to keep in mind when applying the bifactor engagement framework in informal learning spaces.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, students endorse expectancy and task value for school and adopt these constructs for particular subjects and tasks (Bong, 2004;Parrisius et al, 2021). Similarly, students engage with school work in general while simultaneously displaying engaged activities in specific classes (Sinatra et al, 2015;Dierendonck et al, 2020). It is therefore conceivable that generation status can influence school expectancy, task value, and engagement and moderate their effects on learning outcomes.…”
Section: Introductionmentioning
confidence: 99%